Optimal Energy Harvesting Scheme for Power Beacon-Assisted Wireless-Powered Networks - Dinh-Thuan Do (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
In this paper, we consider one-way  relay with energy harvesting system based on power beacon (PB), in which the relay node harvests transmitted power from the PB station to forward signals to destination. We also analyse the relay network model with amplify-and-forward (AF) protocol for information cooperation and Power Splitting-based Relaying (PSR) protocol for power transfer. In particular, the outage probability and optimal energy harvesting (EH) power splitting fraction of novel scheme in are presented. We obtain analytical closed-form expression of  optimal energy harvesting (EH) power splitting fraction to minimize the outage probability of system. Using numerical and analytical simulations, the performances of different cases are presented and discussed.